BZR1 Mediates Brassinosteroid-Induced Autophagy and Nitrogen Starvation in Tomato. Issue 2 (27th November 2018) - Wang, Yu; Cao, Jia-Jian; Wang, Kai-Xin; Xia, Xiao-Jian; Shi, Kai; Zhou, Yan-Hong; Yu, Jing-Quan; Zhou, Jie
Abstract : Brassinosteroid triggers the formation of autophagosomes through induction of the transcription factor brassinazole-resistant1, which involves the regulation of nitrogen starvation tolerance in tomato. Abstract: Autophagy, an innate cellular destructive mechanism, plays crucial roles in plant development and responses to stress. Autophagy is known to be stimulated or suppressed by multiple molecular processes, but the role of phytohormone signaling in autophagy is unclear. Here, we demonstrate that the transcripts of autophagy-related genes ( ATGs ) and the formation of autophagosomes are triggered by enhanced levels of brassinosteroid (BR). Furthermore, the BR-activated transcription factor brassinazole-resistant1 (BZR1), a positive regulator of the BR signaling pathway, is involved in BR-induced autophagy. Treatment with BR enhanced the formation of autophagosomes and the transcripts of ATGs in BZR1 -overexpressing plants, while the effects of BR were compromised in BZR1 -silenced plants. Yeast one-hybrid analysis and chromatin immunoprecipitation coupled with quantitative polymerase chain reaction revealed that BZR1 bound to the promoters of ATG2 and ATG6 . The BR-induced formation of autophagosomes decreased in ATG2 - and ATG6 -silenced plants. Moreover, exogenous application of BR enhanced chlorophyll content and autophagosome formation and decreased the accumulation of ubiquitinated proteins under nitrogen starvation. Leaf chlorosis and chlorophyll degradation were exacerbated in BZR1 -silenced plants and the BR biosynthetic mutant d ^im but were alleviated in BZR1 - and BZR1-1D -overexpressing plants under nitrogen starvation. Meanwhile, nitrogen starvation-induced expression of ATGs and autophagosome formation were compromised in both BZR1 -silenced and d ^im plants but were increased in BZR1 - and BZR1-1D -overexpressing plants. Taken together, our results suggest that BZR1-dependent BR signaling up-regulates the expression of ATGs and autophagosome formation, which plays a critical role in the plant response to nitrogen starvation in tomato ( Solanum lycopersicum ).